The 89,000-Mr murine cytomegalovirus immediate-early protein activates gene transcription. - Koszinowski, U H (1986)
To study trans-activation of gene expression by murine cytomegalovirus (MCMV) immediate-early (IE) proteins, the IE coding region 1 (ie1), which encodes the 89,000-Mr IE phosphoprotein (pp89), was stably introduced into L cells. A cell line was selected and characterized that efficiently expressed the authentic viral protein. The pp89 that was constitutively expressed in L cells stimulated the expression of transfected recombinant constructs containing the bacterial chloramphenicol acetyltransferase (CAT) gene under the control of viral promoters. The regulatory function of the ie1 product was confirmed by transient expression assays in which MCMV IE genes were cotransfected into L cells together with recombinant constructs of the CAT gene. For CAT activation by the ie1 product, a promoter region was required, but there was no preferential activation of a herpes simplex virus type 1 delayed-early promoter. All plasmid constructs that contained the intact coding sequences for pp89 induced gene expression in trans. The MCMV enhancer region was not essential for the expression of a functional IE gene product, and testing of the cis-regulatory activity of the MCMV enhancer revealed a low activity in L cells. Another region transcribed at IE times of infection, IE coding region 2, was unable to induce CAT expression and also did not augment the functional activity of ie1 after cotransfection.